Pengaruh Tuntutan Kerja, Sumber Daya Kerja, dan Kesejahteraan terhadap Kinerja Awak Sarana Perkeretaapian di Pt Kereta Api Indonesia (Persero) - Supriadi Supriadi; Septiana Dwiputrianti; Teni Listiani; Elly Sufiyanti (Jurnal Ilmiah Global Education, 2026)
This study aims to analyze the influence of job demands, sumber daya kerja, and well-being on the Job Performance of Railway Crew Members (Awak Sarana Perkeretaapian/ASP) at PT KAI (Persero). The research model is developed based on the job demands –Resources (JD-R) framework, which emphasizes the balance between workload and available resources in shaping employee performance outcomes. A quantitative approach was employed using a survey method to collect data through online questionnaires distributed to 200 respondents selected with proportionate stratified random sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that job demands have a positive and significant effect on Job Performance, although the effect is relatively small. job resources also have a positive and significant impact on Job Performance, particularly through social support from supervisors and coworkers, as well as the clarity of job objectives carried out by ASP. Meanwhile, employee well-being demonstrates the most dominant influence on Job Performance. The findings confirm the relevance of the JD-R model in the railway operational context and highlight the importance of organizational strategies in balancing high job demands with adequate job resources and well-being initiatives. Practically, these results can serve as a foundation for the company to formulate policies for improving ASP performance through better work schedule management, provision of adequate facilities, career development support, and strengthening of employee well-being programs.